1992
DOI: 10.1061/(asce)0733-9399(1992)118:10(2017)
|View full text |Cite
|
Sign up to set email alerts
|

Tuned Liquid Damper (TLD) for Suppressing Horizontal Motion of Structures

Abstract: A new kind of passive mechanical damper, tuned liquid damper (TLD). is studied that relies upon the motion of shallow liquid in a rigid tank for changing the dynamic characteristics of a structure and dissipating its vibration energy. A nonlinear model of two-dimensional liquid motion inside a rectangular TLD subjected to horizontal motion is developed on the basis of shallow-water wave theory, where the damping of the liquid motion is included semianalytically. Using the model, the response of a structure wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
89
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(107 citation statements)
references
References 18 publications
(19 reference statements)
2
89
0
Order By: Relevance
“…The motion and viscosity of the liquid generate the required damping. This tuned liquid damper (TLD) is cost-effective, easy to install and maintain and requires a very low vibration level to which it will respond, which is sometimes a problem with standard mechanical TMDs [204]. Nakamura and Fujino [156] reported that 600 plastic tanks with 34 mm of water were employed to suppress lateral vibrations of a cable-stayed footbridge.…”
Section: Other Damping Devicesmentioning
confidence: 99%
“…The motion and viscosity of the liquid generate the required damping. This tuned liquid damper (TLD) is cost-effective, easy to install and maintain and requires a very low vibration level to which it will respond, which is sometimes a problem with standard mechanical TMDs [204]. Nakamura and Fujino [156] reported that 600 plastic tanks with 34 mm of water were employed to suppress lateral vibrations of a cable-stayed footbridge.…”
Section: Other Damping Devicesmentioning
confidence: 99%
“…Tuned liquid dampers (TLDs) gained increased popularity due to their effectiveness in absorbing low-frequency vibrations induced by wind, being cost effective, requiring less maintenance, and being easily implementable [11]. TLDs are energy dissipation devices, suggested for vibration suppression under different dynamic loads.…”
Section: Tuned Liquid Dampersmentioning
confidence: 99%
“…This allows significant energy dissipation and hence reduced structural responses [12]. The fundamental principle of vibration control in structures using TLDs is based on sloshing and wave breaking for energy dissipation [11]. For efficient energy dissipation, the fundamental frequency of liquid in a TLD should be close to that of the primary structure.…”
Section: Tuned Liquid Dampersmentioning
confidence: 99%
“…That is, the liquid tank can be used as a damper that the proper tuned liquid tank may mitigate earthquake and wind induced vibration of tall building or long span bridge. Therefore, a liquid tank is also frequently used as a TLD to reduce possible violent oscillation of the structures (Banerji et al [1][2], Sun et al [3], Reed et al [4], Fujino et al [5], and Marivani and Hamed [6]). The simple idea is the sloshing frequency of the liquid in a tank can be tuned to give a desired reaction to reduce the vibration of the structures attached with liquid tanks.…”
Section: Introductionmentioning
confidence: 99%